Surface water quality assessment for sustainable water management in Varsity Lake, University Malaya / Nuzaima Che Mood - Nuzaima , Che Mood (2018)
Surface water quality monitoring is an important tool in the context of sustainable water management system. This study focuses on the comprehensive water quality assessment of Varsity Lake for recreational purposes and to evaluate the suitability of two river tributaries that pass through the University of Malaya (UM) campus in maintaining the lake water level. This work also aims to evaluate the effectiveness of lake rehabilitation and current water management towards sustainable water management inside the campus. Varsity Lake suffers from eutrophication and water quality degradation due to the increase pollution rates, water source scarcity and poor water management. UM management authorities have taken an initiative to improve lake water quality in the lake rehabilitation project. In this study, field and laboratory analysis were conducted to understand the transport of water quality parameters from nine sampling stations located within the campus. Water Quality Index (WQI) was generated using the six parameters, namely Dissolved Oxygen (DO), pH, Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Ammonical Nitrogen (NH3-N), Total Suspended Solids (TSS), and it is used to define the status of water quality. The research also extends towards the nutrient study by including the analysis on the Nitrate (NO3-) and Phosphate (PO43-) concentrations for all sampling stations. Eleven heavy metals parameters, which include Arsenic (As), Aluminum (Al), Cadmium (Cd), Chromium (Cr) , Copper (Cu), Iron (Fe), Lead (Pb), Manganese (Mn), Nickel (Ni), Silver (Ag), and Zinc (Zn) were analyzed using the inductively coupled plasma optical emission spectroscopy (ICP-OES). The data variations were illustrated by Whisker‟s boxplot and further analyzed using the multivariate statistical method to show the nature of the data patterns and the significant difference between the lake and river water quality. Statistical analysis spatially proved that lake and river have different physico-chemical characteristics and lay in separate clusters. The river water that flows in UM campus recorded a higher concentration of metals as compared to the lake. Overall, WQI result shows that lake water is in Class II (82 - 86), while the river is in Class III (65-70). Pantai River has the highest average amount of Pb, Cd and Cu, while Anak Air Batu River has the highest amount of Fe. The current water quality is also compared with the concentration in pre-rehabilitation stage by using six parameters (DO, BOD, TSS, NH3-N, NO3-, and PO43-). From the study, it shows that all parameters were reduced up to 97% and this proved that the rehabilitation works and the current water management is effective in helping to improve the lake water quality. Therefore, the lake rehabilitation method can be used to improve water quality in similar water body.